The youth rationality of working in the tourism in Derawan Island, Berau Regency, East Borneo, Indonesia - Hidayah, Ahmad; Singh, Balraj (Harmoni Sosial: Jurnal Pendidikan IPS, 2021)
This article analyzes the rational choice of working and owning a business in the tourism sector for youth on Derawan Island, Berau Regency, East Borneo. This article uses James S. Coleman's theory of rational choice as a tool to analyze the phenomenon under study. The study uses a qualitative research method (descriptive approach) with youth research on Derawan Island in triangulating analysis. They work or own a business in the tourism sector. The technique of selecting informants in this study was purposive sampling and snowball sampling. Data were obtained through in-depth interviews and observation techniques. The results are that young people on Derawan Island choose to work and have a business in the tourism sector because of several rational reasons: 1.) Seeing the potential of the region; 2.) According to their passion; 3.) Having an income. The same or even more significant than those who work in the formal sector; and 4.) Have more free time.